Improving Dissimilar Metal Joining Quality Through Shielded Metal Arc Welding: A Taguchi Optimization Strategy - Supriyanto, Agus; Sukarman, Sukarman; Mulyadi, Dodi; Djafar Shieddieque, Apang; Abdulah, Amri; Khoirudin, Khoirudin; Apang Djafar Shieddieque (Mechanical Engineering Department Universitas Buana Perjuangan Karawang, 2024)
The results of an experiment that used an orthogonal Taguchi method to improve shielded metal arc welding (SMAW) were given. The SMAW method was used to join dissimilar metal of SPHC and St. 30. SPHC material has a low carbon steel content, while St. 30C steels contain a medium amount of carbon steel, which is used for tractor shaft axles. Carbon percentages vary slightly between the two substances. This study aimed to achieve the highest possible quality of tensile strength by utilizing the specified SMAW parameters. SPHC material has a low carbon content, whereas St. 30 steel has a moderate carbon content. This study used the Taguchi experimental method with three input variables and three experimental levels. The SNR ratio is used to evaluate the most optimal SMAW performance. ANOVA analysis is used to evaluate the most crucial parameters in determining the response variable. This research has successfully provided input on the combination of SPHC and St. 30C for SMEs. It operates effectively with a welding current of 133 A, a welding voltage of 9 V, and a filler diameter of 2.0 mm. The S/N ratio analysis found that the welding current, voltage, and filler diameter all had a significant impact on the outcome.